2017
DOI: 10.1016/j.diagmicrobio.2016.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and characteristics of Escherichia coli sequence type 131 (ST131) from long-term care facility residents colonized intestinally with fluoroquinolone-resistant Escherichia coli

Abstract: The objective of this study was to evaluate molecular and epidemiologic factors associated with Escherichia coli sequence type 131 (ST131) among long-term care facility (LTCF) residents who acquired gastrointestinal tract colonization with fluoroquinolone-resistant E. coli (FQREC). Colonizing isolates from 37 residents who newly developed FQREC colonization at three LTCFs from 2006–2008 were evaluated. Twenty-nine (78%) of 37 total FQREC colonizing isolates were ST131. Most ST131 isolates had a distinctive com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…The proportions of fimH , fyuA , iutA , traT , and PAI genes were similar to those in previous reports [19, 20], although the proportions of hlyA / cnf1 and ompT/sat were different from those reported in previous Korean/Indian and U. S studies [2022]. This result suggests that differences in virulence profiles among ST131 strains may depend on their geographical origin, whether the study was hospital/ “long-term care facility” or community based, and the source of isolates.…”
Section: Discussionsupporting
confidence: 83%
“…The proportions of fimH , fyuA , iutA , traT , and PAI genes were similar to those in previous reports [19, 20], although the proportions of hlyA / cnf1 and ompT/sat were different from those reported in previous Korean/Indian and U. S studies [2022]. This result suggests that differences in virulence profiles among ST131 strains may depend on their geographical origin, whether the study was hospital/ “long-term care facility” or community based, and the source of isolates.…”
Section: Discussionsupporting
confidence: 83%
“…In healthcare centers, Han et al could not identify relevant differences between 29 and 8 long-term care facility (LTCF) residents colonized with ST131 and non-ST131 fluoroquinolone-resistant E. coli . [ 11 ]; in another study in a LTCF, Burgess et al found that time of admission, being unable to sign consent, decubitus ulcer and fecal incontinence were risk factors for colonisation with ciprofloxacin-resistant ST131 E. coli [ 12 ]. Other studies only investigated ESBL-producing ST131 isolates [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, non-ST131 E. coli strains were reported to be just as virulent as some ST131 isolates (Ciesielczuk et al, 2015 ). Though, Cha et al ( 2016 ) recently alleged that the ST131 clone was more virulent than others, Han et al ( 2017 ) showed that ST131 strains fail to excel in aggregate virulence. Furthermore, Dahbi et al ( 2014 ) reported that ST131 isolates show diverse virulence and low-virulence isolates are common among them.…”
Section: The Significance Of Additional Fluoroquinolone Resistance Mementioning
confidence: 99%